LEARNING MOTIVATION OF FOURTH GRADE STUDENTS IN FACING (PAS) FINAL SEMESTER ASSESSMENTS - Rani Dewiningtyas; Endang Sri Maruti; Melik Budiarti (Jurnal Dikdas, 2020)
Learning motivation is an impetus that exists in individuals in learning. In this case motivation is very important. How do students make efforts to be able to develop and increase student learning motivation in class prior to grade promotion (PAS). This study aims to determine the Learning Motivation of Class IV Students in Facing (PAS) Final Semester Assessment. This research uses a qualitative approach to the type of case study. Using Data collection using observation, interview, and documentation techniques. The results showed that in overall fourth grade students of MI Kinandang, Bendo District had quite high motivation to learn when facing (PAS). It can be seen that students' learning motivation is influenced by intrinsic motivation and extrinsic motivation.